Pengaruh kepemilikan manajerial, kepemilikan institusional, profitabilitas, leverage dan kualitas audit terhadap manajemen laba - Ardiyanti Pratika, Aristi; Nurhayati, Ida (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to measure and analyze the effect of managerial ownership, institutional ownership, profitability, leverage and audit quality. This study uses a quantitative approach. In this study, sampling was carried out using a purposive sampling technique. The type of data used in this study is secondary data, namely data obtained indirectly through intermediary media. The secondary data used in this study is in the form of annual financial reports or annual reports of manufacturing companies listed on the IDX for the 2018-2020 period. The sample criteria set by the author are 223 companies with a number of years of observation for 3 years, then outliers are carried out so as to produce a research sample of 180 companies. The results of this study are managerial ownership and audit quality have no effect on earnings management, institutional ownership and profitability have a positive effect on earnings management, while leverage has a negative effect on earnings management.